The characterisation and future sustainability of a rural landscape: using integrated approaches for temporal heritage landscape analysis in Northwest Spain - Hearn, Kyle P.; Fagerholm, Nora (SPRINGER, 2025)
Context Changing global socioeconomics are endangering agrosilvopastoral landscapes and with them the knowledge of maintaining these historical, sustainable forms of territorial management. Approaches that integrate Local Spatial Knowledge (LSK) with scientific methods are valuable means to understand their landscape heritage, identity, and temporal land use and land cover (LULC).
Objectives Our aim is to utilise an interdisciplinary approach that combines 'bottom-up' ethnographic/participatory studies with 'top-down' Historic Landscape Characterisation (HLC) to characterise and analyse past and present LULC changes and evaluate the future sustainability of a rural cultural landscape case study.
Methods We mapped LULC between the 1900s and the 2010s in a case study in NW Spain. Our approach initially utilised a landscape perception study and participatory mapping of LSK. These ethnographic data were integrated into the HLC temporal maps to characterise and analyse LULC evolution. Using the HLC maps, a statistical analysis of temporal changes of landscape attributes was completed.
Results The perception study revealed a decline in biodiversity and agrosilvopastoralism. Participatory mapping generated new spatial data of historical land cover and land use traditions indicative of multifunctional rural landscapes. HLC maps, utilising empirical sources and participatory data, corroborated ethnographic perceptions of a loss of landscape multifunctionality due to depopulation.
Conclusions This integrative approach underscores a landscape marked by abandonment, increased vegetative growth, nature conservation measures, and wildfires. This study highlights the value of inter and transdisciplinary approaches to analyse and understand temporal landscape change. The research's newly created spatial data can be used as a potential planning tool for sustainable rural development, adaptation to climate change, and heritage conservation.